The Influence of Dynamic Capabilities on Innovation and Competitive Advantage: A Study of Sago Processed MSMEs in Meranti Islands Regency - Andri; Samsir; Siregar, Prima Andreas (MultiTech Publisher, 2024)
This study examines the influence of dynamic capabilities on innovation and competitive advantage in sago processed MSMEs in the Meranti Islands Regency. The sample consisted of 95 sago-processing MSMEs located in the Meranti Islands Regency. This study highlights the importance of dynamic capabilities in a VUCA (volatile, uncertain, complex, and ambiguous) business environments. The study argues that MSMEs must develop dynamic capabilities to adapt to a rapidly changing environment and survive intense competition. This study identifies three dimensions of dynamic capabilities: sensing, seizing, and transformation. Sensing capability enables companies to detect environmental changes and new market opportunities, while seizing capability helps them capture and exploit these opportunities. Transforming capabilities allow companies to change their existing activities and resources to produce competitive advantages. The study also emphasizes the role of innovation in increasing competitive advantage. Innovation helps companies meet consumer needs and desires, attract new customers, and retain existing customers. Overall, the study suggests that dynamic capabilities and innovation are critical factors for MSMEs to gain a competitive advantage in the Meranti Islands Regency sago industry